SHASHMAKOM’S PLACE AND AESTHETIC VALUE IN ART. - Jo'rayeva Dilnoza Faxriddin qizi; Erkinov Mirshoxid To'lqin o'g'li (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
One of the masterpieces of the centuries-old musical culture of the Uzbek people, Shashmaqom, is not only the highest example of national music but also a priceless treasure of the entire Eastern civilization. The term “Shashmaqom” comes from Persian-Tajik and means “six maqoms.” It consists of six major maqoms — Buzruk, Rost, Navo, Dugoh, Segoh, and Iroq — each distinguished by its unique melodic structure, spiritual mood, and artistic meaning.